2019
DOI: 10.1002/aelm.201900493
|View full text |Cite
|
Sign up to set email alerts
|

MXene Quantum Dot/Polymer Hybrid Structures with Tunable Electrical Conductance and Resistive Switching for Nonvolatile Memory Devices

Abstract: Emerging polymer memory devices with resistive switching are promising alternatives to existing conventional random access memory technology due to their ability of information storage and process. [1-4] An effective strategy to realize resistive switching for memory effect is organicinorganic hybrid design in polymer device, with the merits of tailorable components, tunable properties, solution process and low-cost manufacturing. [5-8] In the organicinorganic hybrid systems, insulating or semiconducting polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 35 publications
(50 reference statements)
1
41
0
Order By: Relevance
“…In another recent study, the MXene-based piezoelectric sensor was studied by Wang et al and found that better dipole polarization of PVDF-TrFE is obtained because of improved conductivity resulting from the higher static electric field force 23 . The hydrophilic properties of MXene attributed to the presence of the surface terminations are reported to promote the dispersion of MXene in the water-soluble polymer 24 . In addition to the aforementioned approaches to improve the electrical performance of nanogenerators, different MXene concentrations will be explored to identify the optimum device performance.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study, the MXene-based piezoelectric sensor was studied by Wang et al and found that better dipole polarization of PVDF-TrFE is obtained because of improved conductivity resulting from the higher static electric field force 23 . The hydrophilic properties of MXene attributed to the presence of the surface terminations are reported to promote the dispersion of MXene in the water-soluble polymer 24 . In addition to the aforementioned approaches to improve the electrical performance of nanogenerators, different MXene concentrations will be explored to identify the optimum device performance.…”
Section: Introductionmentioning
confidence: 99%
“…With their intriguing advantages, perovskite QDs have been widely used for many applications in light-emitting diodes (QLEDs), 7 solar cells, 8 photodetectors, 9 resistive switching memory and other electronic devices. 10 In particular, through the modification of the CsPbX 3 QDs and optimization of the device structure, the external quantum efficiency (EQE) of the CsPbX 3 -QD-based electroluminescent (EL) LED devices has been significantly improved from the first reported value of 0.12% to 21%. 11,12 Even though perovskite QDs have made great progress in QLED devices, [13][14][15][16] the surface defects of perovskite QDs are still the main problem hindering their further practical application.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity of the device jumps to LRS, and the high current density ohmic transmission at this stage may be attributed to the conductive filament. TFLC is the transition stage from OC to SCLC in the presence of multiple traps, but the two polymers PF and PCz have no trap effect, which is absent from this conduction region. …”
Section: Resultsmentioning
confidence: 99%